Critical masses and critical choices: evolving public opinion on nuclear weapons, terrorism, and security - Herron, Kerry G. (University of Pittsburgh Press)
Objectives, concepts, and theories -- Trends in nuclear security assessments -- Trends in policy and spending preferences -- Terrorism -- Opinion stability at the individual level -- Mass belief structures -- Making sense of public beliefs and preferences about security policy -- Appendix 1: Research methodology -- Appendix 2: Questions, distributions, and means